Crystalline polyaryletherketone surface grafted carbon fiber and preparation method thereof

By using technical means such as sulfonation reaction and "one-pot" polymerization on the carbon fiber production line, crystalline polyaryletherketone is efficiently grafted on the surface of the carbon fiber, solving the problems of long reaction cycles of traditional methods and the materials that are not resistant to high temperature and corrosion, and achieving better high temperature and corrosion resistance.

CN119591939AActive Publication Date: 2025-03-11JILIN UNIVERSITY

Patent Information

Application Number
CN202411679557.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-11
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently realize the chemical bond graft between crystalline polyaryletherketone and carbon fiber on the carbon fiber production line, and the traditional method has a long reaction period and the chemical agent used is not resistant to high temperatures and corrosion.

Method used

The sulfone-containing amino capping agent was prepared by sulfonation reaction, and the agent was polymerized by "one-pot" method to prepare amino capping polyarylether. Then, through diazon salt reaction and electrochemical reduction reaction, the polyarylether is efficiently grafted on the surface of the carbon fiber, and finally hydrolyzed under an acidic environment to obtain crystalline polyaryletherketone surface grafted carbon fibers.

Benefits of technology

The chemical bond grafting between crystalline polyaryletherketone and carbon fiber is achieved efficiently and at low cost on the carbon fiber production line, reducing the reaction cycle, and the grafted polyaryletherketone has better resistance to high temperature and corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591939A_ABST
    Figure CN119591939A_ABST
Patent Text Reader

Abstract

The invention discloses a crystalline polyaryletherketone surface grafted carbon fiber and a preparation method thereof, and belongs to the technical field of carbon materials.The preparation method comprises the following steps that an amino end-capping reagent containing sulfuryl, a difluoro monomer, a bisphenol monomer and potassium carbonate are placed in sulfolane to be subjected to a polymerization reaction, and amino-terminated polyarylether is obtained; carrying out diazonium salt reaction on the amino-terminated polyarylether and nitrite tetrafluoroborate to obtain diazonium salt-terminated polyarylether; connecting the carbon fiber with a cathode, immersing the carbon fiber in an electrolyte containing diazonium salt terminated polyarylether, and applying a reduction potential for reaction to obtain polyarylether grafted carbon fiber; and carrying out hydrolysis reaction on the carbon fiber grafted with polyarylether in an acid environment to obtain the crystalline polyaryletherketone surface grafted carbon fiber. According to the crystalline polyaryletherketone surface grafting modified carbon fiber prepared by the invention, the carbon fiber is directly connected with a polymer through high-temperature-resistant and corrosion-resistant phenyl and sulfuryl, so that the crystalline polyaryletherketone surface grafting modified carbon fiber has better high-temperature resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon materials, in particular to a crystalline polyaryletherketone surface-grafted carbon fiber and a preparation method thereof. Background Art

[0002] Carbon fiber reinforced resin-based composite materials are often used in various fields such as sea, land, air and space due to their high specific strength and specific modulus, and face a wide variety of harsh service environments. Its service capability depends on the type of resin base. Crystalline polyaryletherketone, as a special engineering plastic, has advantages such as chemical stability, corrosion resistance (insoluble in common organic solvents such as tetrahydrofuran, nitrogen methyl pyrrolidone, halogenated hydrocarbons at room temperature), water resistance and high temperature resistance (taking polyetheretherketone as an example, its crystallization melting temperature is 343 ° C), and is a resin matrix with excellent performance. However, the above advantages of crystalline polyaryletherketone also bring about the problem of poor interfacial bonding ability with carbon fiber, which will cause the weak interfacial phase to become a short board and reduce the performance of the composite material. In order to improve the interfacial properties of carbon fiber and crystalline polyaryletherketone, the interaction between the two needs to be enhanced. Chemical bonds are the strongest interaction, so grafting crystalline polyaryletherketone on the surface of carbon fiber through chemical bonds is one of the effective means to enhance the interfacial interaction between the two. There are four problems in grafting crystalline polyaryletherketone on the surface of carbon fiber through chemical bonds: (1) In order to ensure that the interface phase has good compatibility with the resin matrix and that the interface phase also has the same corrosion resistance and high temperature resistance as the resin matrix, it is necessary to graft crystalline polyaryletherketone onto the carbon fiber surface; (2) The excellent corrosion resistance of crystalline polyaryletherketone results in the lack of effective solvents, making it difficult for effective chemical reactions to occur in the solid phase; (3) Functional groups such as ester bonds, amide bonds, aliphatic ether bonds and alkyl groups are usually not resistant to high temperatures, and their decomposition temperatures are usually less than or equal to 300 °C, which cannot meet the molding requirements of crystalline polyaryletherketone at 400 °C. Therefore, grafting needs to be achieved through stable and high-temperature resistant chemical bonds; (4) To ensure the continuity of carbon fiber, chemical bond grafting must be efficiently achieved on the carbon fiber production line.

[0003] A lot of work on carbon fiber surface modification based on chemical bond grafting has been carried out both at home and abroad, but none of them can solve the above problems at the same time. For example, CN103806281B discloses a carbon fiber surface grafting method through carbon fiber surface oxidation, chlorination (public basic knowledge: anhydrous environment is required) and esterification (public basic knowledge: anhydrous environment is required), which is difficult to implement continuously on the carbon fiber production line, and the ester group cannot meet the processing conditions of crystalline polyaryletherketone at 400°C; CN105131332B discloses a carbon fiber surface grafting method based on azide-based alkyne click chemistry reaction, in which the carbon fiber is oxidized, treated with a silane coupling agent, and chemical bond grafting is achieved after azidation and click chemistry reaction. However, this method not only has a long surface reaction cycle, but also requires a large amount of highly toxic and highly explosive sodium azide (200-500g of sodium azide is required to prepare 1kg of carbon fiber), and its industrialization potential is low; CN118087246A discloses a carbon fiber surface modification method based on electrochemical free radical surface polymerization, but since polyaryletherketone cannot be prepared by free radical polymerization, this method is not suitable for polyaryletherketone resin matrix. CN104195835B discloses a method for grafting polyethyleneimine onto the surface of carbon fiber by supercritical treatment, but supercritical treatment requires a high pressure of 5-7 MPa, which places extremely high demands on equipment. In addition, the grafted polymers of the above invention are not resistant to high temperatures and are not compatible with crystalline polyaryletherketone.

[0004] CN106192366B discloses a carbon fiber surface grafting method based on a triazine structure. Although the triazine structure can withstand a high temperature of 400°C, the reaction cycle of the triazine structure requires 20-40 hours, and it is difficult to implement on a carbon fiber production line; CN114318878B discloses a grafting method based on "thiol-ene" click chemistry to graft polyphenylene sulfide onto the carbon fiber surface. However, the alkyl CS chemical bond generated by the "thiol-ene" click chemistry is also not stable at 400°C; CN112457629B discloses a carbon fiber surface grafting method using an aminosilane coupling agent and an imidization reaction. Although the imide structure has a high thermal stability, the alkyl and CN bonds in the silane coupling agent may become weak links at high temperatures; CN110820315B discloses a method for grafting carbon fiber surface by electrochemical reduction of carbon fiber surface alkynylation, sizing agent alkynylation, hydrolysis, and alkyne thermal crosslinking. This method successfully uses thermally stable chemical bonds to graft crystalline polyaryletherketone on the carbon fiber surface, but the monomer of this method is expensive (such as requiring a palladium catalyst) and the synthesis is complex (such as low activity of the end-capping agent, resulting in the need to first polymerize and then end-cap the sizing agent). Relatedly, CN113105620B discloses a method for preparing amino-terminated polyaryletherketone, using an amino-terminated agent containing a benzophenone structure, and preparing amino-terminated polyaryletherketone by a two-step method (first polymerizing and then end-capping), which is due to the low activity of the amino-terminated agent containing a benzophenone structure. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing carbon fibers grafted onto the surface of crystalline polyaryletherketone to solve the problems raised in the above-mentioned background technology.

[0006] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions: A method for preparing crystalline polyaryletherketone surface grafted carbon fiber, comprising the following steps: The sulfonyl chloride compound containing a nitro group and a halogenated benzene are subjected to a sulfonation reaction and a reduction reaction in sequence to obtain an amino-terminated agent containing a sulfone group; The amino-terminated agent containing a sulfone group, a difluoro monomer, a bisphenol monomer and potassium carbonate are placed in sulfolane to carry out a polymerization reaction to obtain an amino-terminated polyarylether; The amino-terminated polyarylether is reacted with nitrite tetrafluoroborate to obtain a diazonium salt-terminated polyarylether; The diazonium salt-terminated polyarylether is prepared into an electrolyte, the carbon fiber is connected to a cathode, immersed in the electrolyte containing the diazonium salt-terminated polyarylether, and a reduction potential is applied to react to obtain a carbon fiber grafted with the polyarylether; The carbon fiber grafted with polyarylether is subjected to a hydrolysis reaction in an acidic environment to obtain a crystalline carbon fiber grafted with polyaryletherketone.

[0007] Preferably, the nitro-containing sulfonyl chloride compound is at least one of nitrobenzenesulfonyl chloride, 4-nitrobiphenyl-4-sulfonyl chloride and 4-(4-nitrophenoxy)benzenesulfonyl chloride; and the halogenated benzene is chlorobenzene or fluorobenzene.

[0008] Preferably, the step of sequentially subjecting a nitro-containing sulfonyl chloride compound and a halogenated benzene to a sulfonation reaction and a reduction reaction to obtain an amino-capping agent containing a sulfone group specifically comprises: Under the condition of no more than -5 ℃ and inert gas protection, the nitro-containing sulfonyl chloride compound is fully dissolved in the halogenated benzene, and AlCl3 powder is added in batches; then the temperature is raised to room temperature and stirred; the temperature is continued to be raised to reflux; deionized water is added to azeotropic reflux to separate the unreacted halogenated benzene; filtering and washing the filter residue to obtain a crude product; using ethanol to recrystallize the crude product three times, and drying to obtain a capping agent precursor; After dissolving the capping agent precursor in methanol, adding tin chloride dihydrate to the solution and refluxing; then filtering and collecting the filtrate, adjusting the pH value of the filtrate to not less than 9 using a saturated aqueous solution of Na2CO3; extracting the mixture twice with ethyl acetate, combining the organic phases and drying with anhydrous sodium sulfate; then filtering, collecting the filtrate and removing the solvent to obtain an amino capping agent containing a sulfone group.

[0009] Preferably, the difluoro monomer is 4,4'-difluorobenzophenone imine and / or difluorodiketone imine; and the bisphenol monomer is at least one of hydroquinone, biphenol, 4,4'-dihydroxybenzophenone and 4,4'-dihydroxydiphenyl ether.

[0010] Preferably, the step of placing an amino-terminated agent containing a sulfone group, a difluoro monomer, a bisphenol monomer and potassium carbonate in sulfolane for polymerization to obtain an amino-terminated polyarylether specifically comprises: The amino end-capping agent containing sulfone group, difluoro monomer, bisphenol monomer and potassium carbonate are dissolved in cyclopentane sulfone at the same time; then toluene is added, the temperature is raised to azeotropic, and after toluene is refluxed for a certain period of time, the toluene is exhausted; the temperature is continued to be raised to not less than 210°C for reaction; then the material is discharged into ethanol, crushed, washed, and dried to obtain amino end-capped polyarylether.

[0011] Preferably, the step of reacting the amino-terminated polyarylether with nitrosotetrafluoroborate to form a diazonium salt to obtain the diazonium salt-terminated polyarylether comprises: The amino-terminated polyarylether is dissolved in 1,4-dioxane; the above solution is added dropwise into an acetonitrile solution containing nitrite tetrafluoroborate; when the solution becomes a dark brown transparent solution, the material is discharged into ether, and the diazonium-terminated polyarylether is rapidly precipitated, which is filtered and washed with ether to obtain the diazonium-terminated polyarylether.

[0012] Preferably, the step of preparing an electrolyte containing diazonium salt-terminated polyarylether, connecting the carbon fiber to the cathode, immersing the carbon fiber in the electrolyte containing diazonium salt-terminated polyarylether, applying a reducing potential to react, and obtaining a carbon fiber grafted with polyarylether specifically comprises: The diazonium salt-terminated polyarylether and supporting electrolyte are dissolved in acetonitrile to prepare an electrolyte solution; The carbon fiber is connected to the cathode, immersed in an electrolyte, and a reduction potential is applied to react. The electrochemically reduced carbon fiber is washed with acetonitrile and dried to obtain a carbon fiber grafted with polyarylether.

[0013] Preferably, the supporting electrolyte is tetrabutylammonium tetrafluoroborate.

[0014] Preferably, the step of hydrolyzing the carbon fiber grafted with polyarylether in an acidic environment to obtain the crystalline polyaryletherketone surface-grafted carbon fiber specifically comprises: The carbon fiber grafted with polyarylether is placed in acetone, hydrochloric acid is added dropwise, and the temperature is raised to reflux; then, the mixture is filtered, washed, and dried to obtain the crystalline polyaryletherketone surface grafted modified carbon fiber.

[0015] Another object of the present invention is to provide a crystalline polyaryletherketone surface-grafted carbon fiber prepared by the above preparation method.

[0016] The present invention provides a method for preparing crystalline polyaryletherketone surface-grafted carbon fibers, wherein an amino-terminated agent containing a sulfone group is prepared, and the amino-terminated agent containing a sulfone group is used to realize a "one-pot method" for preparing amino-terminated polyarylether and diazonium-terminated polyarylether; the surface of the carbon fibers is modified by using the diazonium-terminated polyarylether, and the carbon fibers can be directly connected to the polymer via the high-temperature and corrosion-resistant phenyl and sulfone groups, and the polyaryletherketone grafted on the surface of the carbon fibers has crystallinity.

[0017] The raw materials used in the present invention are relatively cheap. The prepared amino end-capping agent containing a sulfone group can avoid the end-capping polymerization of "polymerization first and then end-capping" due to its high reactivity, realize the "one-pot" end-capping polymerization, and reduce the reaction cycle (omitting 2-6 hours of the post-end-capping process).

[0018] The crystalline polyaryletherketone surface grafted modified carbon fiber prepared by the present invention has better high temperature resistance and corrosion resistance because the carbon fiber is directly connected to the polymer through the high temperature and corrosion resistant phenyl and sulfone groups, avoiding the ester group and other functional groups that are not resistant to high temperature and corrosion used in the traditional mechanism. In addition, since the crystalline polyaryletherketone is grafted to the surface of the carbon fiber through a chemical bond, it has better corrosion resistance.

[0019] The preparation method provided by the present invention avoids traditional esterification, amidation and other reactions, and uses electrochemical reduction as a grafting method. Due to the high reaction efficiency (3-5 min), it is possible to achieve batch preparation of crystalline polyaryletherketone surface grafted modified carbon fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the structural formula of the carbon fiber grafted with polyarylether obtained in the embodiment of the present invention; Figure 2 is the structural formula of the crystalline polyaryletherketone surface grafted carbon fiber obtained in the embodiment of the present invention; Figure 3 This is a Raman spectrum characterization result diagram of the crystalline polyaryletherketone surface grafted carbon fiber prepared in an embodiment of the present invention; Figure 4 The cyclic voltammetry curve of the electrochemical reduction grafting reaction provided by the embodiment of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] The embodiment of the present invention firstly prepares an amino-terminated agent containing a diphenyl sulfone structure by a sulfonation reaction using a low-cost reagent, and utilizes its high reactivity (the higher the electron-withdrawing ability of the para-functional group of fluorobenzene, the higher the substitution reaction activity, which is reflected in the significantly lower polymerization activity of 4,4'-difluorobenzophenone than that of 4,4'-difluorodiphenyl methyl sulfone) to achieve the "one-pot" polymerization of amino-terminated polymers; on this basis, directly construct a diazonium salt functional group at the polymer end group, and efficiently achieve the purpose of grafting the polymer on the carbon fiber surface by an electrochemical reduction reaction (1-5 min). Finally, the polymer grafted on the carbon fiber surface is converted into a crystalline polyaryletherketone by a hydrolysis reaction. The embodiment of the present invention achieves carbon fiber surface grafting by high-temperature resistant phenylene and sulfone groups.

[0023] The end-capping agent used in the embodiment of the present invention is characterized by: using a diphenyl sulfone structure constructed by a sulfonation reaction as a primitive, wherein the para position of one phenyl group is replaced by a fluorine or chlorine atom, and the para position of another phenyl group is directly or indirectly connected to an aniline functional group. Among them, the sulfone group is located in the para position of the fluorine (chlorine) atom, which can significantly improve the reaction efficiency of the end-capping agent and can achieve "one-pot" end-capping polymerization. Its synthesis method is: using a nitro-containing sulfonyl chloride compound and a halogenated benzene as raw materials, preparing an end-capping agent precursor through a sulfonation reaction; reducing the nitro group to an amino group through a reduction reaction (the reducing agent is SnCl2) to prepare the end-capping agent. The specific reaction route is as follows: ; Wherein, X is F or Cl; The structural formula is: ; Correspondingly, The structural formula is: .

[0024] The amino-terminated polyarylether prepared in the embodiment of the present invention is characterized in that the amino-terminated polyarylether is directly prepared by "one-pot" polymerization, and the polymer main chain is connected to the aniline end group through the sulfone group. The "one-pot" polymerization method is: the end-capping agent, the difluoro monomer, the bisphenol monomer and potassium carbonate are dissolved in sulfolane (solvent) at the same time, and the amino-terminated polyarylether is obtained by polymerization after azeotropic dehydration. The specific reaction route is as follows: ; Wherein, the structural formula of bisphenol monomer is any one of the following: ; .

[0025] The structural formula of the difluoro monomer is any of the following: .

[0026] The amino-terminated polyarylether has a structural formula of any of the following:

[0027] ; Wherein, the structural formula of R is any of the following: .

[0028] The diazonium salt-terminated polyarylether prepared in the embodiment of the present invention is characterized in that the polymer main chain is connected to the phenyl tetrafluoroborate diazonium salt end group through a sulfone group. The implementation method is: the diazonium salt-terminated polyarylether is prepared by reacting nitrosotetrafluoroborate with the diazonium salt of the aniline end group. The specific reaction route is as follows:

[0029] Wherein, the structural formula of the diazonium salt-terminated polyarylether is any one of the following:

[0030] ; Wherein, the structural formula of R1 is any of the following: .

[0031] The polyarylether surface grafted modified carbon fiber prepared in the embodiment of the present invention is characterized in that the carbon fiber surface is directly connected to the polyarylether through the phenyl and sulfone groups through an efficient electrochemical reduction reaction. The specific method is: connect the carbon fiber to the cathode of the electrolytic cell, immerse it in an electrolyte (containing diazonium salt-terminated polyarylether), apply a reduction potential to react, wash and dry to obtain the carbon fiber grafted with polyarylether, and its structural formula is as follows: Figure 1 shown. Figure 1 In the invention, the structural formula of the polyarylether is any one of the following:

[0032] .

[0033] The polyaryletherketone surface grafted modified carbon fiber prepared in the embodiment of the present invention is characterized in that the carbon fiber surface is directly connected to the crystalline polyaryletherketone through the phenyl group and the sulfone group, and the method is: the carbon fiber grafted with polyarylether is hydrolyzed in an acidic environment to form crystalline polyaryletherketone, thereby obtaining the crystalline polyaryletherketone surface grafted carbon fiber, and its structure is as follows: Figure 2 shown. Figure 2 In the invention, the structural formula of the crystalline polyaryletherketone is any one of the following:

[0034]

[0035] ; in addition, Figure 1 and Figure 2 In the formula of R2, any of the following is true: .

[0036] Specifically, in one embodiment of the present invention, a method for preparing carbon fiber grafted on the surface of crystalline polyaryletherketone is provided, which comprises the following steps: S1. Under the condition of no more than -5 °C and inert gas protection, fully dissolve the nitro-containing sulfonyl chloride compound in halogenated benzene (both as solvent and reactant), and add AlCl3 powder in batches; then heat to room temperature and stir for 3-5 hours; continue to heat to reflux and stir for 8-10 hours; add deionized water to azeotropic reflux to separate the unreacted halogenated benzene; filter, and wash the filter residue with NaOH solution (0.5-1.5 mol / L) and deionized water in turn to obtain a crude product; recrystallize the crude product with ethanol three times, and dry to obtain a capping agent precursor; S2. After dissolving the end-capping agent precursor in methanol (0.01-0.1 mol / L), add tin chloride dihydrate (5 times the molar amount of the end-capping agent precursor) to the solution, and reflux for 5-7 hours; then filter and collect the filtrate, and adjust the pH value of the filtrate to not less than 9 using a saturated aqueous solution of Na2CO3; extract the mixture twice with ethyl acetate, combine the organic phases and dry them with anhydrous sodium sulfate; then filter, collect the filtrate and remove the solvent to obtain an amino end-capping agent containing a sulfone group; S3, dissolving the amino end-capping agent containing sulfone group, difluoro monomer, bisphenol monomer and potassium carbonate in cyclopentane sulfone (solvent) at the same time; then adding toluene, heating to azeotropic (130-150 ° C), maintaining toluene reflux for 3-5 hours, and then draining the toluene; continuing to heat to not less than 210 ° C for reaction, maintaining for 3-5 hours; then discharging into ethanol, crushing, and washing with ethanol and water for 3 times each, and drying to obtain amino end-capped polyarylether; S4, dissolving the amino-terminated polyarylether in 1,4-dioxane (amino end group equivalent 0.01-0.1 mol / L); dropping the above solution into an acetonitrile solution (0.01-0.1 mol / L) containing nitrite tetrafluoroborate (NOBF4); when the solution becomes a dark brown transparent solution, discharging the solution into ether, rapidly precipitating the diazonium-terminated polyarylether, filtering and washing with ether to obtain the diazonium-terminated polyarylether; S5. Dissolve the diazonium salt-terminated polyarylether (0.01-0.1 g / mL) and the supporting electrolyte (0.5-1.5 mM) in acetonitrile to prepare an electrolyte; connect the carbon fiber to the cathode, immerse it in the electrolyte, and apply a reduction potential of -0.3 V for 1-5 min. Wash the electrochemically reduced carbon fiber with acetonitrile and dry it to obtain a carbon fiber grafted with polyarylether; S6. Place the carbon fiber grafted with polyarylether in acetone (0.01-0.05 g / mL), and add 1-3 M hydrochloric acid in an equal volume to the acetone, raise the temperature to reflux, and maintain for 20-28 hours; then filter, wash with deionized water for several times, and dry to obtain crystalline polyaryletherketone surface grafted modified carbon fiber.

[0037] The nitro-containing sulfonyl chloride compound is at least one of nitrobenzenesulfonyl chloride, 4-nitrobiphenyl-4-sulfonyl chloride and 4-(4-nitrophenoxy)benzenesulfonyl chloride; the halogenated benzene is chlorobenzene or fluorobenzene, preferably fluorobenzene. The difluoro monomer is 4,4'-difluorobenzophenone imine and / or difluorodiketone imine; the bisphenol monomer is at least one of hydroquinone, biphenol, 4,4'-dihydroxybenzophenone and 4,4'-dihydroxydiphenyl ether. The supporting electrolyte is tetrabutylammonium tetrafluoroborate.

[0038] The following embodiments are some specific implementation cases and application cases of the present invention in practical applications, but are not limited thereto.

[0039] Example 1: This example provides a method for preparing carbon fibers grafted onto the surface of crystalline polyaryletherketone, which specifically comprises the following steps: (1) Under the protection of inert gas at -5 °C, nitrobenzenesulfonyl chloride (0.1 mol) was fully dissolved in chlorobenzene (chlorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted chlorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (4-chloro-4'-nitrodiphenyl sulfone, corresponding to the above chemical formula: R'= R'-1; X= Cl) was obtained by recrystallization three times with ethanol and drying. The yield was 85%; (2) After dissolving the end-capping agent precursor (4-chloro-4'-nitrodiphenyl sulfone) obtained in step (2) in methanol (0.01 mol / L), tin chloride dihydrate (0.05 mol / L) was added to the solution; refluxed for 6 h; filtered and collected the filtrate, and the pH value of the filtrate was adjusted to 9 using a saturated aqueous solution of Na2CO3; the mixture was extracted twice with ethyl acetate, and the organic phases were combined and dried over anhydrous sodium sulfate; filtered, collected the filtrate and removed the solvent to obtain the end-capping agent (4-chloro-4'-aminodiphenyl sulfone, corresponding to the above chemical formula: R''= R''-1; X= Cl), with a yield of 95%; (3) 0.001 mol of the end-capping agent (4-chloro-4'-aminodiphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorobenzophenone imine, 0.1 mol of hydroquinone and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the material is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetheretherketoneimine (corresponding to the above chemical formula: NH2-PI-1; R=R1-1); (4) dissolving the amino-terminated polyetheretherketoneimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether ether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated polyetheretherketoneimine (corresponding to the above chemical formula: Dia-PI-1; R1=R1-1); (5) The diazonium salt-terminated polyetheretherketoneimine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) were dissolved in acetonitrile as an electrolyte; the carbon fiber was connected to the cathode of the electrolytic cell and immersed in the electrolyte; a reduction potential of -0.3 V was applied and maintained for 3 min to perform an electrochemical reduction grafting reaction. The cyclic voltammetry curve of the electrochemical reduction grafting reaction is shown in FIG. Figure 4 As shown; the electrochemically reduced carbon fiber is washed with acetonitrile and dried to obtain a carbon fiber grafted with polyetheretherketimine (corresponding to the above chemical structure: PI-1; R2-=R2-1); (6) The carbon fiber grafted with polyetheretherketone imine obtained in step (5) was placed in acetone (0.01 g / mL); 2 M hydrochloric acid in an equal volume to acetone was added dropwise; the temperature was raised to reflux and maintained for 24 h; the carbon fiber was filtered and washed with deionized water three times, and dried to obtain crystalline polyetheretherketone surface grafted modified carbon fiber (corresponding to the above chemical structure: P-1; R2-=R2-1). The crystalline polyetheretherketone surface grafted modified carbon fiber obtained above was characterized by Raman spectroscopy, and the results were as follows: Figure 3 As shown, the results show that crystalline poly(aryletherketone) was successfully grafted onto the surface of carbon fiber.

[0040] Example 2: This example provides a method for preparing a crystalline polyaryletherketone surface grafted carbon fiber, which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4-nitrobiphenyl-4-sulfonyl chloride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.15 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 5 hours; the mixture was heated to reflux and stirred for 10 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone, corresponding to the above chemical formula: R'= R'-2; X=F) was obtained by recrystallization three times with ethanol and drying. The yield was 88%; (2) After dissolving the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone) obtained in step (1) in methanol (0.1 mol / L), tin chloride dihydrate (0.5 mol / L) was added to the solution; refluxed for 6 h; filtered and collected the filtrate, and the pH value of the filtrate was adjusted to 9 using a saturated aqueous solution of Na2CO3; the mixture was extracted twice with ethyl acetate, and the organic phases were combined and dried over anhydrous sodium sulfate; filtered, collected the filtrate and removed the solvent to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl) diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X= F), with a yield of 95%; (3) 0.02 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorobenzophenone imine, 0.1 mol of 4,4'-dihydroxydiphenyl ether and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the product is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetheretherketoneimine (corresponding to the above chemical formula: NH2-PI-2; R=R-3); (4) dissolving the amino-terminated polyetheretheretherketoneimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.1 mol / L); adding the above solution dropwise into an acetonitrile solution (0.1 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated polyetheretherketoneimine (corresponding to the above chemical formula: Dia-PI-2; R1=R1-3); (5) Dissolving the diazonium salt-terminated polyetheretherketoneimine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) in acetonitrile as an electrolyte; connecting the carbon fiber to the cathode of the electrolytic cell and immersing it in the electrolyte; applying a reduction potential of -0.3 V for 3 min; washing the electrochemically reduced carbon fiber with acetonitrile and drying it to obtain a carbon fiber grafted with polyetheretherketoneimine (corresponding to the above chemical structure: PI-2; R2=R2-3); (6) The carbon fiber grafted with polyetheretheretherketoneimine obtained in step (5) is placed in acetone (0.05 g / mL); an equal volume of 2 M hydrochloric acid is added dropwise; the temperature is raised to reflux and maintained for 24 h; the mixture is filtered, washed three times with deionized water, and dried to obtain a crystalline polyetheretheretherketone surface grafted modified carbon fiber (corresponding to the above chemical structure: P-2; R2=R2-3).

[0041] Example 3: This example provides a method for preparing a crystalline polyaryletherketone surface-grafted carbon fiber, which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4-(4-nitrophenoxy)benzenesulfonyl chloride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (4-fluoro-4'-(4-nitrophenoxy)diphenyl sulfone, corresponding to the above chemical formula: R'=R'-3; X=F) was obtained by recrystallization three times with ethanol and drying. The yield was 85%; (2) After dissolving the end-capping agent precursor (4-fluoro-4'-(4-nitrophenoxy) diphenyl sulfone) obtained in step (1) in methanol (0.01 mol / L), tin chloride dihydrate (0.05 mol / L) was added to the solution; refluxed for 6 h; filtered and collected the filtrate, and the pH value of the filtrate was adjusted to 9 using a saturated aqueous solution of Na2CO3; the mixture was extracted twice with ethyl acetate, and the organic phases were combined and dried over anhydrous sodium sulfate; filtered, collected the filtrate and removed the solvent to obtain the end-capping agent (4-fluoro-4'-(4-aminophenoxy) diphenyl sulfone, corresponding to the above chemical formula: R''= R''-3; X= F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenoxy)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorodiketone imine, 0.1 mol of 4,4'-dihydroxydiphenyl ether and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the product is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetheretheretherketoneketimine (corresponding to the above chemical formula: NH2-PI-6; R=R-2); (4) dissolving the amino-terminated poly(ether-ether-ketone-ketone-imine) obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated poly(arylether) is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated poly(ether-ether-ketone-ketone-imine) (corresponding to the above chemical formula: Dia-PI-6; R1=R1-2); (5) Dissolving the diazonium salt-terminated polyetheretheretherketoneketimine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) in acetonitrile as an electrolyte; connecting the carbon fiber to the cathode of the electrolytic cell and immersing it in the electrolyte; applying a reduction potential of -0.3 V for 3 min; washing the electrochemically reduced carbon fiber with acetonitrile and drying it to obtain a carbon fiber grafted with polyetheretheretherketoneketimine (corresponding to the above chemical structure: PI-6; R2=R2-2); (6) The carbon fiber grafted with polyetheretheretherketoneketoneimine obtained in step (5) is placed in acetone (0.01 g / mL); an equal volume of 2 M hydrochloric acid is added dropwise to the acetone; the temperature is raised to reflux and maintained for 24 h; the mixture is filtered, washed three times with deionized water, and dried to obtain a crystalline polyetheretheretherketoneketone surface-grafted modified carbon fiber (corresponding to the above chemical structure: P-6; R2=R2-2).

[0042] Example 4: This example provides a method for preparing carbon fibers grafted onto the surface of crystalline polyaryletherketone, which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4-nitrobiphenyl-4-sulfonyl chloride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone, corresponding to the above chemical formula: R'= R'-2; X=F) was obtained by recrystallization three times with ethanol and drying. The yield was 86%; (2) After dissolving the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone) obtained in step (1) in methanol (0.01 mol / L), tin chloride dihydrate (0.05 mol / L) was added to the solution; refluxed for 6 h; filtered and collected the filtrate, and the pH value of the filtrate was adjusted to 9 using a saturated aqueous solution of Na2CO3; the mixture was extracted twice with ethyl acetate, and the organic phases were combined and dried over anhydrous sodium sulfate; filtered, collected the filtrate and removed the solvent to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl) diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X= F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorobenzophenone imine, 0.1 mol of 4,4'-dihydroxybenzophenone and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the product is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetherketone imine (corresponding to the above chemical formula: NH2-PI-4; R=R-3); (4) dissolving the amino-terminated polyetherketoneimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether ether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated polyetherketoneimine (corresponding to the above chemical formula: Dia-PI-4; R1=R1-3); (5) The diazonium salt-terminated polyetherketimine (0.01 g / mL) obtained in step (4) and the supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) were dissolved in acetonitrile as an electrolyte; the carbon fiber was connected to the cathode of the electrolytic cell and immersed in the electrolyte; a reduction potential of -0.3 V was applied and maintained for 5 min; the electrochemically reduced carbon fiber was washed with acetonitrile and dried to obtain a carbon fiber grafted with polyetherketimine (corresponding to the above chemical structure: PI-4; R2=R2-3); (6) The carbon fiber grafted with polyetherketone imine obtained in step (5) is placed in acetone (0.01 g / mL); an equal volume of 2 M hydrochloric acid is added dropwise; the temperature is raised to reflux and maintained for 24 h; the mixture is filtered, washed three times with deionized water, and dried to obtain a crystalline polyetherketone surface grafted carbon fiber (corresponding to the above chemical structure: P-4; R2=R2-3).

[0043] Example 5: This example provides a method for preparing a crystalline polyaryletherketone surface-grafted carbon fiber, which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4-nitrobiphenyl-4-sulfonyl chloride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone, corresponding to the above chemical formula: R'= R'-2; X=F) was obtained by recrystallization three times with ethanol and drying. The yield was 86%; (2) After dissolving the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone) obtained in step (1) in methanol (0.01 mol / L), tin chloride dihydrate (0.05 mol / L) was added to the solution; refluxed for 6 h; filtered and collected the filtrate, and the pH value of the filtrate was adjusted to 9 using a saturated aqueous solution of Na2CO3; the mixture was extracted twice with ethyl acetate, and the organic phases were combined and dried over anhydrous sodium sulfate; filtered, collected the filtrate and removed the solvent to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl) diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X= F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorodiketone imine, 0.1 mol of hydroquinone and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the material is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetheretherketoneketimine (corresponding to the above chemical formula: NH2-PI-5; R=R-3); (4) dissolving the amino-terminated polyetheretherketoneketimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated polyetheretherketoneketimine (corresponding to the above chemical formula: Dia-PI-5; R1=R1-3); (5) Dissolving the diazonium salt-terminated polyetheretherketoneketimine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) in acetonitrile as an electrolyte; connecting the carbon fiber to the cathode of the electrolytic cell and immersing it in the electrolyte; applying a reduction potential of -0.3 V for 4 min; washing the electrochemically reduced carbon fiber with acetonitrile and drying it to obtain a carbon fiber grafted with polyetheretherketoneketimine (corresponding to the above chemical structure: PI-5; R2-=R2-3); (6) The carbon fiber grafted with polyetheretherketoneketoneimine obtained in step (5) is placed in acetone (0.01 g / mL); an equal volume of 2 M hydrochloric acid is added dropwise; the temperature is raised to reflux and maintained for 24 h; the mixture is filtered, washed three times with deionized water, and dried to obtain a crystalline polyetheretherketoneketone surface-grafted modified carbon fiber (corresponding to the above chemical structure: P-5; R2=R2-3).

[0044] Example 6: This example provides a method for preparing a crystalline polyaryletherketone surface-grafted carbon fiber, which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4-nitrobiphenyl-4-sulfonyl chloride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone, corresponding to the above chemical formula: R'= R'-2; X=F) was obtained by recrystallization three times with ethanol and drying. The yield was 86%; (2) After dissolving the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone) obtained in step (1) in methanol (0.01 mol / L), tin chloride dihydrate (0.05 mol / L) was added to the solution; refluxed for 6 h; filtered and collected the filtrate, and the pH value of the filtrate was adjusted to 9 using a saturated aqueous solution of Na2CO3; the mixture was extracted twice with ethyl acetate, and the organic phases were combined and dried over anhydrous sodium sulfate; filtered, collected the filtrate and removed the solvent to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl) diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X= F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorobenzophenone imine, 0.1 mol of biphenyl diphenol and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the material is washed with ethanol and water three times each, and dried to obtain amino-terminated biphenyl type polyetheretherketone imine (corresponding to the above chemical formula: NH2-PI-3; R=R-3); (4) dissolving the amino-terminated biphenyl polyetheretherketone imine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether ether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated biphenyl polyetheretherketone imine (corresponding to the above chemical formula: Dia-PI-3; R1=R1-3); (5) The diazonium salt-terminated biphenyl polyetheretherketone imine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) were dissolved in acetonitrile as an electrolyte; the carbon fiber was connected to the cathode of the electrolytic cell and immersed in the electrolyte; a reduction potential of -0.3 V was applied and maintained for 3 min; the electrochemically reduced carbon fiber was washed with acetonitrile and dried to obtain a carbon fiber grafted with biphenyl polyetheretherketone imine (corresponding to the above chemical structure: PI-3; R2=R2-3); (6) The carbon fiber grafted with biphenyl polyetheretherketone imine obtained in step (5) is placed in acetone (0.01 g / mL); an equal volume of 2 M hydrochloric acid is added dropwise; the temperature is raised to reflux and maintained for 24 h; the mixture is filtered, washed three times with deionized water, and dried to obtain a crystalline biphenyl polyetheretherketone surface grafted modified carbon fiber (corresponding to the above chemical structure: P-3; R2=R2-3).

[0045] Example 7: This example provides a method for preparing a crystalline polyaryletherketone surface-grafted carbon fiber, which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4-nitrobiphenyl-4-sulfonyl chloride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl)diphenyl sulfone, corresponding to the above chemical formula: R'= R'-2; X=F) was obtained by recrystallization three times with ethanol and drying. The yield was 86%.

[0046] (2) After dissolving the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone) obtained in step (1) in methanol (0.01 mol / L), tin chloride dihydrate (0.05 mol / L) was added to the solution; refluxed for 6 h; filtered and collected the filtrate, and the pH value of the filtrate was adjusted to 9 using a saturated aqueous solution of Na2CO3; the mixture was extracted twice with ethyl acetate, and the organic phases were combined and dried over anhydrous sodium sulfate; filtered, collected the filtrate and removed the solvent to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl) diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X= F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorodiketone imine, 0.1 mol of biphenyl diphenol and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the product is washed with ethanol and water three times each, and dried to obtain amino-terminated biphenyl type polyetheretherketoneketimine (corresponding to the above chemical formula: NH2-PI-7; R=R-3); (4) dissolving the amino-terminated biphenyl polyetheretherketoneketimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated biphenyl polyetheretherketoneketimine (corresponding to the above chemical formula: Dia-PI-7; R1=R1-3); (5) The diazonium salt-terminated biphenyl polyether ether ketone ketimine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) were dissolved in acetonitrile as an electrolyte; the carbon fiber was connected to the cathode of the electrolytic cell and immersed in the electrolyte; a reduction potential of -0.3 V was applied and maintained for 3 min; the electrochemically reduced carbon fiber was washed with acetonitrile and dried to obtain a carbon fiber grafted with biphenyl polyether ether ketone ketimine (corresponding to the above chemical structure: PI-7; R2-=R2-3); (6) The carbon fiber grafted with biphenyl polyetheretherketoneketoneimine obtained in step (5) is placed in acetone (0.01 g / mL); an equal volume of 2 M hydrochloric acid is added dropwise; the temperature is raised to reflux and maintained for 24 h; the mixture is filtered, washed three times with deionized water, and dried to obtain a crystalline biphenyl polyetheretherketoneketone surface-grafted modified carbon fiber (corresponding to the above chemical structure: P-7; R2=R2-3).

[0047] Example 8: This example provides a method for preparing a crystalline polyaryletherketone surface-grafted carbon fiber, which specifically comprises the following steps: (1) At -5 °C and under inert gas protection, 4-nitrobiphenyl-4-sulfonyl chloride (0.1 mol) was fully dissolved in fluorobenzene (fluorobenzene was used as both solvent and reactant), and AlCl3 powder (0.12 mol) was added in 5 batches; the mixture was heated to room temperature and stirred for 3 hours; the mixture was heated to reflux and stirred for 8 hours; deionized water was added to azeotropically reflux and unreacted fluorobenzene was separated; the mixture was filtered and the residue (crude product) was washed with NaOH solution (1 mol / L) and deionized water in turn; the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone, corresponding to the above chemical formula: R'= R'-2; X=F) was obtained by recrystallization three times with ethanol and drying. The yield was 86%; (2) After dissolving the end-capping agent precursor (4-fluoro-4'-(4-nitrophenyl) diphenyl sulfone) obtained in step (1) in methanol (0.01 mol / L), tin chloride dihydrate (0.05 mol / L) was added to the solution; refluxed for 6 h; filtered and collected the filtrate, and the pH value of the filtrate was adjusted to 9 using a saturated aqueous solution of Na2CO3; the mixture was extracted twice with ethyl acetate, and the organic phases were combined and dried over anhydrous sodium sulfate; filtered, collected the filtrate and removed the solvent to obtain the end-capping agent (4-fluoro-4'-(4-aminophenyl) diphenyl sulfone, corresponding to the above chemical formula: R''= R''-2; X=F), with a yield of 95%; (3) 0.01 mol of the end-capping agent (4-fluoro-4'-(4-aminophenyl)diphenyl sulfone) obtained in step (2), 0.1 mol of 4,4'-difluorodiketone imine, 0.1 mol of 4,4'-dihydroxybenzophenone and 0.13 mol of potassium carbonate are added to cyclopentane sulfone (solvent) at the same time; toluene is added, the temperature is raised to azeotropic (130°C), toluene and water are maintained at azeotropic reflux for 4 hours, and toluene is exhausted; the temperature is raised to 210°C and maintained for 4 hours; the material is discharged into ethanol and crushed; the product is washed with ethanol and water three times each, and dried to obtain amino-terminated polyetherketoneetherketoneketoneimine (corresponding to the above chemical formula: NH2-PI-8; R=R-3); (4) dissolving the amino-terminated polyetherketoneetherketoneketoneimine obtained in step (3) in 1,4-dioxane (amino end group equivalent 0.01 mol / L); adding the above solution dropwise into an acetonitrile solution (0.01 mol / L) containing 1.5 times the amino end group equivalent of tetrafluoroborate nitrite; when the solution becomes a dark brown transparent solution, discharging the solution into ether, the diazonium salt-terminated polyarylether ether is rapidly precipitated, filtered and washed with ether to obtain a diazonium salt-terminated polyetherketoneetherketoneketoneimine (corresponding to the above chemical formula: Dia-PI-8; R1=R1-3); (5) Dissolving the diazonium salt-terminated polyetherketoneetherketoneketoneimine (0.01 g / mL) obtained in step (4) and a supporting electrolyte (tetrabutylammonium tetrafluoroborate, 1 mM) in acetonitrile as an electrolyte; connecting the carbon fiber to the cathode of the electrolytic cell and immersing it in the electrolyte; applying a reduction potential of -0.3 V for 3 min; washing the electrochemically reduced carbon fiber with acetonitrile and drying it to obtain a carbon fiber grafted with polyetherketoneetherketoneketoneimine (corresponding to the above chemical structure: PI-8; R2=R2-3); (6) The carbon fiber grafted with polyetherketoneetherketoneketoneimine obtained in step (5) is placed in acetone (0.01 g / mL); an equal volume of 2 M hydrochloric acid is added dropwise to the acetone; the temperature is raised to reflux and maintained for 24 h; the mixture is filtered, washed three times with deionized water, and dried to obtain a crystalline polyetherketoneetherketoneketone surface-grafted modified carbon fiber (corresponding to the above chemical structure: P-8; R2-=R2-3).

[0048] Based on the above-mentioned ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above-mentioned description. The technical scope of the present invention is not limited to the contents of the specification.

Claims

1. A method for preparing carbon fiber grafted on the surface of crystalline polyaryletherketone, characterized in that: The following steps are involved: The sulfonyl chloride compound containing a nitro group and a halogenated benzene are subjected to a sulfonation reaction and a reduction reaction in sequence to obtain an amino-terminated agent containing a sulfone group; The amino-terminated agent containing a sulfone group, a difluoro monomer, a bisphenol monomer and potassium carbonate are placed in sulfolane to carry out a polymerization reaction to obtain an amino-terminated polyarylether; The amino-terminated polyarylether is reacted with nitrite tetrafluoroborate to obtain a diazonium salt-terminated polyarylether; The diazonium salt-terminated polyarylether is prepared into an electrolyte, the carbon fiber is connected to a cathode, immersed in the electrolyte containing the diazonium salt-terminated polyarylether, and a reduction potential is applied to react to obtain a carbon fiber grafted with the polyarylether; The carbon fiber grafted with polyarylether is subjected to a hydrolysis reaction in an acidic environment to obtain a crystalline carbon fiber grafted with polyaryletherketone.

2. The method for preparing crystalline polyaryletherketone surface-grafted carbon fiber according to claim 1, characterized in that: The nitro-containing sulfonyl chloride compound is at least one of nitrobenzenesulfonyl chloride, 4-nitrobiphenyl-4-sulfonyl chloride and 4-(4-nitrophenoxy)benzenesulfonyl chloride; and the halogenated benzene is chlorobenzene or fluorobenzene.

3. The method for preparing crystalline polyaryletherketone surface-grafted carbon fiber according to claim 1 or 2, characterized in that: The step of sequentially subjecting a nitro-containing sulfonyl chloride compound and a halogenated benzene to a sulfonation reaction and a reduction reaction to obtain an amino end-capping agent containing a sulfone group specifically comprises: Under the condition of no more than -5 ℃ and inert gas protection, the nitro-containing sulfonyl chloride compound is fully dissolved in the halogenated benzene, and AlCl3 powder is added in batches; then the temperature is raised to room temperature and stirred; the temperature is continued to be raised to reflux; deionized water is added to azeotropic reflux to separate the unreacted halogenated benzene; filtering and washing the filter residue to obtain a crude product; using ethanol to recrystallize the crude product three times, and drying to obtain a capping agent precursor; After dissolving the capping agent precursor in methanol, adding tin chloride dihydrate to the solution and refluxing; then filtering and collecting the filtrate, adjusting the pH value of the filtrate to not less than 9 using a saturated aqueous solution of Na2CO3; extracting the mixture twice with ethyl acetate, combining the organic phases and drying with anhydrous sodium sulfate; then filtering, collecting the filtrate and removing the solvent to obtain an amino capping agent containing a sulfone group.

4. The method for preparing crystalline polyaryletherketone surface-grafted carbon fiber according to claim 1, characterized in that: The difluoro monomer is 4,4'-difluorobenzophenone imine and / or difluorodiketone imine; the bisphenol monomer is at least one of hydroquinone, biphenol, 4,4'-dihydroxybenzophenone and 4,4'-dihydroxydiphenyl ether.

5. The method for preparing crystalline polyaryletherketone surface-grafted carbon fiber according to claim 1 or 4, characterized in that: The step of placing an amino-terminated agent containing a sulfone group, a difluoro monomer, a bisphenol monomer and potassium carbonate in sulfolane for polymerization reaction to obtain an amino-terminated polyarylether specifically comprises: The amino end-capping agent containing sulfone group, difluoro monomer, bisphenol monomer and potassium carbonate are dissolved in cyclopentane sulfone at the same time; then toluene is added, the temperature is raised to azeotropic, and after toluene is refluxed for a certain period of time, the toluene is exhausted; the temperature is continued to be raised to not less than 210°C for reaction; then the material is discharged into ethanol, crushed, washed, and dried to obtain amino end-capped polyarylether.

6. The method for preparing crystalline polyaryletherketone surface-grafted carbon fiber according to claim 1, characterized in that: The step of subjecting the amino-terminated polyarylether to a diazonium salt reaction with nitrosotetrafluoroborate to obtain the diazonium salt-terminated polyarylether specifically comprises: The amino-terminated polyarylether is dissolved in 1,4-dioxane; the above solution is added dropwise into an acetonitrile solution containing nitrite tetrafluoroborate; when the solution becomes a dark brown transparent solution, the material is discharged into ether, and the diazonium-terminated polyarylether is rapidly precipitated, which is filtered and washed with ether to obtain the diazonium-terminated polyarylether.

7. The method for preparing crystalline polyaryletherketone surface-grafted carbon fiber according to claim 1, characterized in that: The steps of preparing an electrolyte containing diazonium salt-capped polyarylether, connecting the carbon fiber to a cathode, immersing the carbon fiber in the electrolyte containing the diazonium salt-capped polyarylether, applying a reducing potential for reaction, and obtaining a carbon fiber grafted with polyarylether, specifically include: The diazonium salt-terminated polyarylether and supporting electrolyte are dissolved in acetonitrile to prepare an electrolyte solution; The carbon fiber is connected to the cathode, immersed in an electrolyte, and a reduction potential is applied to react. The electrochemically reduced carbon fiber is washed with acetonitrile and dried to obtain a carbon fiber grafted with polyarylether.

8. The method for preparing crystalline polyaryletherketone surface-grafted carbon fiber according to claim 7, characterized in that: The supporting electrolyte is tetrabutylammonium tetrafluoroborate.

9. The method for preparing crystalline polyaryletherketone surface-grafted carbon fiber according to claim 1, characterized in that: The step of hydrolyzing the carbon fiber grafted with polyarylether in an acidic environment to obtain the crystalline polyaryletherketone surface grafted carbon fiber specifically comprises: The carbon fiber grafted with polyarylether is placed in acetone, hydrochloric acid is added dropwise, and the temperature is raised to reflux; then, the mixture is filtered, washed, and dried to obtain the crystalline polyaryletherketone surface grafted modified carbon fiber.

10. A crystalline polyaryletherketone surface-grafted carbon fiber prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method of Grafting Hyperbranched Polyglycerol on Carbon Fiber Surface to Improve Interfacial Properties of Composite Materials

    CN103806281B

  • A method for grafting polymers on the surface of carbon fibers under supercritical conditions

    CN104195835B

  • A method for modifying carbon fiber by surface grafting polymer

    CN105131332B

  • A method for grafting triazine dendritic molecules on the surface of carbon fibers

    CN106192366B

  • A crystalline crosslinkable polyaryletherketone sizing agent modified carbon fiber and its preparation method

    CN110820315B

Cited By

  • Laminated composite material toughening intermediate layer and preparation method thereof

    CN120700696A

  • Cross-linked polymer modified carbon fiber, preparation method and composite material

    CN121363113A

  • A crosslinked polymer-modified carbon fiber, a preparation method and a composite material

    CN121363113B

  • Recovery method of polyaryletherketone material based on green primary amine compound

    CN122404796A

  • Process for recycling polyaryletherketone materials based on green primary amine compounds

    CN122404796B